2022
DOI: 10.1002/aic.17846
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics and mass transfer enhancement of gas–liquid flow in micropacked bed reactors: Effect of contact angle

Abstract: Pressure drop, residence time distribution, dispersive behavior, liquid holdup, and mass transfer performance of gas–liquid flow in micropacked bed reactors (μPBRs) with different contact angles (CA) of particles are studied. The value of pressure drop for three types of beads can be obtained: copper beads (CA = 88.1°) > stainless steel beads (CA = 70.2°) > glass beads (CA = 47.1°). The liquid axial dispersion coefficient is 1.58 × 10−6 to 1.07 × 10−5 m2/s for glass beads and copper beads, which is smaller tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…21 In addition, our group employed the hydrogenation of α-methylstyrene system in the μPBR with Pd catalysts to obtain the external mass transfer performance of gas-liquid-solid reaction. 22 Wang et al 23 evaluated the effect of particle wettability on gas-liquid effective interfacial area of the μPBR and revealed that large contact angle was helpful for enhancing mass transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In addition, our group employed the hydrogenation of α-methylstyrene system in the μPBR with Pd catalysts to obtain the external mass transfer performance of gas-liquid-solid reaction. 22 Wang et al 23 evaluated the effect of particle wettability on gas-liquid effective interfacial area of the μPBR and revealed that large contact angle was helpful for enhancing mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In the above-mentioned studies, all results were obtained and calculated by variation of reactor inlet and outlet gas/liquid concentrations, representing the average values of mass transfer performance in the whole μPBR. [17][18][19][20][21][22][23] Nevertheless, the local differences of gasliquid flow behavior existed because of the sophisticated inner status inside the μPBR, 24 which induced the heterogeneous mass transfer in temporal and spatial dimensions possibly. The study of local mass transfer performance contributed to improve all-around understanding and guide the reactor optimization.…”
Section: Introductionmentioning
confidence: 99%